Ethiopia : Urban Labor Markets, Challenges and Prospects, Volume 1. Synthesis Report - World Bank (Washington, DC, 2012)
This report focuses on a central element of Ethiopia's challenge: the urban labor market. The headlines, which are detailed in the report, are dramatic, and include the following: open unemployment has been persistently high and average duration is long, though recent trends suggest improved performance. There is a significant segmentation-two relatively privileged sector in the public and formal private sectors, a massive informal sector and a large stock of unemployed. Individual transitions across these states have increased over time, but remain relatively limited. Formal sector employment in urban areas is dominated by the state and manufacturing sector employment remains among the lowest in the world. The majority of those who are working in urban areas are engaged in informal sector activity, typically as a last resort but also as a persistent state. Average wages are low, especially for the unskilled and in the informal sector, but productivity is also very low. Women are especially disadvantaged in the labor market-and typically face worse outcomes with higher levels of unemployment, lower wages, and a greater concentration in the informal sector. Many youth seem to enter the labor market through low quality jobs in the informal sector or into unemployment. The structure of this report is as follows. Volume I synthesizes the emerging findings and policy implications while Volume 2 presents a series of thematic chapters which summarize the underlying background work. In this volume the next chapter sets the stage for the analysis by clarifying the metrics of the key labor market indicators. Chapter 3 looks at the structure of urban labor markets and what has hindered their ability to generate jobs despite the acceleration of growth in the last few years. Chapter 4 focuses on the challenge of urban unemployment, while Chapter 5 looks at the effects of migration on urban labor markets. The final chapter in this volume reviews the emerging policy agenda.